2015
DOI: 10.1186/s12872-015-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell control of thrombosis

Abstract: Hemostasis encompasses a set of tightly regulated processes that govern blood clotting, platelet activation, and vascular repair. Upon vascular injury, the hemostatic system initiates a series of vascular events and activates extravascular receptors that act in concert to seal off the damage. Blood clotting is subsequently attenuated by a plethora of inhibitors that prevent excessive clot formation and eventual thrombosis. The endothelium which resides at the interface between the blood and surrounding tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
438
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(486 citation statements)
references
References 113 publications
10
438
0
8
Order By: Relevance
“…12 Reduced venous wall shear stress induces hypoxia and stimulates release of P-selectin and von Willebrand factor (vWF) from endothelial cells thus promoting thrombus formation. 13 Once the endothelial cells become activated they play an essential role in the generation of thrombin through the expression of procoagulant factors that contribute to both the initiation and propagation of thrombus generation.…”
Section: Endothelial Dysfunction and Vtmentioning
confidence: 99%
“…12 Reduced venous wall shear stress induces hypoxia and stimulates release of P-selectin and von Willebrand factor (vWF) from endothelial cells thus promoting thrombus formation. 13 Once the endothelial cells become activated they play an essential role in the generation of thrombin through the expression of procoagulant factors that contribute to both the initiation and propagation of thrombus generation.…”
Section: Endothelial Dysfunction and Vtmentioning
confidence: 99%
“…Nandi and Brown Platelet-mimetic strategies for modulating the wound environment 1139 of a fibrin clot. 7 These events occur alongside primary hemostasis, but rather than facilitating platelet aggregation, they induce the formation of an insoluble fibrin clot through the binding of the pro-coagulant tissue factor (TF) molecule to coagulation factor fVII, forming a TF/fVII complex that can cleave factorX into factorXa, a molecule that generates thrombin. Thrombin activates the adherent platelet aggregate, allowing several other pro-coagulant factors to bind to the surface of the aggregate.…”
Section: Platelets In Coagulation and Hemostasismentioning
confidence: 99%
“…10,12 The fibrin mesh and platelet aggregate form a complete clot that can prevent further blood loss. 7,13 Following the cessation of bleeding, cytoplasmic motility proteins, including actin and myosin, facilitate platelet clot contraction, resulting in expulsion of serum from the clot. 14 The contractile forces generated by the platelet-rich plasma within the clot increases with time, forming a seal at the clot site to fortify the hemostatic capabilities of the clot.…”
Section: Platelets In Coagulation and Hemostasismentioning
confidence: 99%
See 1 more Smart Citation
“…21 Impairment of endothelial function triggers the platelet adhesion and aggregation, and fibrin formation that play a critical role in systematic hypercoagulability. Several recent reports suggested that endothelial NOS downregulation in the LA was associated with the development of LA thrombi formation even in the presence of sinus rhythm.…”
Section: Endothelial Function As Clinical Risk Stratificationmentioning
confidence: 99%